Isolation and characterization of a novel pathogenic strain of Ehrlichia minasensis - de Aguiar, Daniel Moura; Junior, João Pessoa Araújo [UNESP]; Nakazato, Luciano; Bard, Emilie; Aguilar-Bultet, Lisandra; Vorimore, Fabien; Popov, Vsevolod Leonidovich; Colodel, Edson Moleta; Cabezas-Cruz, Alejandro (MDPI, 2019)
The genus Ehrlichia is composed of tick-borne obligate intracellular gram-negative alphaproteobacteria of the family Anaplasmataceae. Ehrlichia includes important pathogens affecting canids (E. canis, E. chaffeensis, and E. ewingii), rodents (E. muris), and ruminants (E. ruminantium). Ehrlichia minasensis, an Ehrlichia closely related to E. canis, was initially reported in Canada and Brazil. This bacterium has now been reported in Pakistan, Malaysia, China, Ethiopia, South Africa, and the Mediterranean island of Corsica, suggesting that E. minasensis has a wide geographical distribution. Previously, E. minasensis was found to cause clinical ehrlichiosis in an experimentally infected calf. The type strain E. minasensis UFMG-EV was successfully isolated from Rhipicephalus microplus ticks and propagated in the tick embryonic cell line of Ixodes scapularis (IDE8). However, the isolation and propagation of E. minasensis strains from cattle has remained elusive. In this study, the E. minasensis strain Cuiabá was isolated from an eight-month-old male calf of Holstein breed that was naturally infected with the bacterium. The calf presented clinical signs and hematological parameters of bovine ehrlichiosis. The in vitro culture of the agent was established in the canine cell line DH82. Ehrlichial morulae were observed using light and electron microscopy within DH82 cells. Total DNA was extracted, and the full genome of the E. minasensis strain Cuiabá was sequenced. A core-genome-based phylogenetic tree of Ehrlichia spp. and Anaplasma spp. confirmed that E. minasensis is a sister taxa of E. canis. A comparison of functional categories among Ehrlichia showed that E. minasensis has significantly less genes in the ‘clustering-based subsystems’ category, which includes functionally coupled genes for which the functional attributes are not well understood. Results strongly suggest that E. minasensis is a novel pathogen infecting cattle. The epidemiology of this Ehrlichia deserves further attention because these bacteria could be an overlooked cause of tick-borne bovine ehrlichiosis, with a wide distribution.
Keywords: Anaplasmataceae; Bovine ehrlichiosis; DH82; Ehrlichia minasensis; Genome; Transmission electron microscopy